HUBUNGAN KONSTITUSI DENGAN TUGAS DAN FUNGSI NEGARA - Mu’allifin, M. Darin Arif (Ahkam: Jurnal Hukum Islam, 2016)
A state’s constitution basically is a promise to be fulfilled. It has an important role in a state’s life cycle. In management, constitution is considered as a system which functions as law planning, law organizing, law actuating, and law controlling to achieve the state’s ideals and objectives. Because of its fundamental role, when a systemic problem occurs, constitution reform, institution reform, and cultural reform can be a choice to solve the problem. Kata kunci: Konstitusi, Reformasi, Institusi